2021
DOI: 10.2298/tsci200704239t
|View full text |Cite
|
Sign up to set email alerts
|

Determination and measurement of some thermophysical properties of nanofluids and comparison with literature studies

Abstract: The thermophysical properties of nanofluids must be determined to evaluate their thermal performances like heat transfer, convection heat transfer coefficient, Nusselt number. The purpose of this study is to obtain the thermophysical properties of nanofluids. Al2O3, TiO2, and ZnO are used as a nanoparticle, while deionized water is used as base fluid. The solutions included nanoparticles in a way to be each with 0.5%, 0.7%, and 1.0% volumetric concentration were prepared. SDS was added to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Hence, suspension of solid particles in fluids can improve the thermal conductivity, in comparison to conventional heat transfer fluids. It was found that the nanofluids that contain or nanoparticles, in ethylene or water, can provide enhanced thermal conductivity [93,94].…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Hence, suspension of solid particles in fluids can improve the thermal conductivity, in comparison to conventional heat transfer fluids. It was found that the nanofluids that contain or nanoparticles, in ethylene or water, can provide enhanced thermal conductivity [93,94].…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Under laminar flow conditions, Arulprakasajothi et al [21] investigated the Nusselt number and friction factor behaviour in a tube heat exchanger with staggered and non-staggered conical strips, finding that the staggered conical strip with a twist ratio of Y = 3 and 0.5 % volume concentration of nanofluid provided the best heat transfer. Topuz et al [22] investigated the thermophysical characteristics of Al 2 O 3 , TiO 2 , and ZnO nanofluids using deionized water and observed that their thermal conductivity is proportional to temperature. The viscosity is related to volumetric concentrations but inversely proportional to temperature at the same time.…”
Section: Introductionmentioning
confidence: 99%